2017
DOI: 10.3389/fonc.2017.00145
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-Mesenchymal Transition in the Female Reproductive Tract: From Normal Functioning to Disease Pathology

Abstract: Epithelial-to-mesenchymal transition (EMT) is a physiological process that is vital throughout the human lifespan. In addition to contributing to the development of various tissues within the growing embryo, EMT is also responsible for wound healing and tissue regeneration later in adulthood. In this review, we highlight the importance of EMT in the development and normal functioning of the female reproductive organs (the ovaries and the uterus) and describe how dysregulation of EMT can lead to pathological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 247 publications
(336 reference statements)
1
100
0
Order By: Relevance
“…Furthermore, TGFβ signaling is crucial for the epithelial to mesenchymal transition (EMT), in which cells lose their epithelial characteristics and acquire migratory behavior (28). EMT is necessary for the development and normal functioning of female reproductive organs such as the ovaries and the uterus and dysregulation may cause endometriosis, adenomyosis, and carcinogenesis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TGFβ signaling is crucial for the epithelial to mesenchymal transition (EMT), in which cells lose their epithelial characteristics and acquire migratory behavior (28). EMT is necessary for the development and normal functioning of female reproductive organs such as the ovaries and the uterus and dysregulation may cause endometriosis, adenomyosis, and carcinogenesis (29).…”
Section: Discussionmentioning
confidence: 99%
“…(Li, VandenBoom et al 2009, Chang, Chao et al 2011. Low levels of miR-200 in addition to a decrease in e-cadherin results in an increase in vimentin, n-cadherin, twist and snail (Bilyk, Coatham et al 2017). Overexpression of leb-7b suppresses cancer cell growth (Xu, Liu et al 2014, Yu, Feng et al 2015 and therefore, may be one of the mechanisms by which C/EBPδ controls the fallopian tube epithelial cell cycle.…”
Section: C/ebpδ Induces An Emt Regulatory Phenotypementioning
confidence: 99%
“…intestine (Tetteh et al 2016), liver, pancreas (Tritschler et al 2017), hair follicles (Merrell and Stanger 2016)) in vivo. Endometrial cells were also reported to be highly plastic (Bilyk et al 2017). Evidences already exist that EMT and MET involved in the menstrual regeneration and embryo implantation in the uterus (Bilyk et al 2017).…”
Section: Our Atlas Highlighted a Emt Program In The Epithelial Subsetmentioning
confidence: 99%
“…Endometrial cells were also reported to be highly plastic (Bilyk et al 2017). Evidences already exist that EMT and MET involved in the menstrual regeneration and embryo implantation in the uterus (Bilyk et al 2017). Subpopulation of MET cells in the regeneration zone that express both epithelial marker cytokeratin and stromal cell marker vimentin was involved in the menstrual endometrial regeneration (Patterson et al 2013).…”
Section: Our Atlas Highlighted a Emt Program In The Epithelial Subsetmentioning
confidence: 99%
See 1 more Smart Citation